2009
DOI: 10.1016/j.neulet.2009.06.034
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism in the 3′UTR of the SNCA gene encoding alpha-synuclein is a new potential susceptibility locus for Parkinson disease

Abstract: In Parkinson disease, the second most common neurodegenerative disorder in humans, increased alpha-synuclein (SNCA) levels are pathogenic, as evidenced by gene copy number mutations and increased alpha-synuclein levels detected in some familial and sporadic PD cases, respectively. Gene expression can be regulated at the post-transcriptional level by elements in the 3′ untranslated region (3′UTR) of mRNAs. The goal of this study was to determine whether the 3′UTR of human SNCA can affect gene expression. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 27 publications
5
66
0
1
Order By: Relevance
“…A logistic regression analysis using the allele dosage of the most associated SNP in each block as a covariate, did not change the results observed at the most associated signal in the other, indicating that the two signals are independent (Supplementary Table 2) and being in disagreement with previous results. 7,25,32 LD analysis between these two SNPs revealed a r 2 value of 0.028 and a D' value of 0.388, further supporting this hypothesis.…”
Section: Sncasupporting
confidence: 58%
See 2 more Smart Citations
“…A logistic regression analysis using the allele dosage of the most associated SNP in each block as a covariate, did not change the results observed at the most associated signal in the other, indicating that the two signals are independent (Supplementary Table 2) and being in disagreement with previous results. 7,25,32 LD analysis between these two SNPs revealed a r 2 value of 0.028 and a D' value of 0.388, further supporting this hypothesis.…”
Section: Sncasupporting
confidence: 58%
“…[6][7][8][25][26][27][28][29][30][31][32] The data presented here supports the hypothesis that two different signals in these blocks are present in the Dutch population, which is in controversy with previous results. 7,28,[30][31][32] In a report by Mueller et al, 25 the authors also detected two association signals in the 3¢ and 5¢ blocks of SNCA. Interestingly, when stratifying their cohort into males and females, as well as young and old PD groups (according to the median age of 57 years), additional significant association in the intron 4 region of the 5¢ block was found for the female and the young patients' subgroups.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Increasing evidence suggests that dysregulated miRNAs directly contribute to the pathogenesis of a variety of human diseases [30][31][32][33][34]. SNPs in miRNA target sites in the 3' UTR of mRNAs are referred to as polymorphisms in microRNAs and their target sites (polymiRTSs) and can affect mRNA half-life, resulting in decreased protein levels due to mRNAmiRNA interactions and increased susceptibility to many diseases [30-33, 35, 36], including PD [33].…”
Section: Discussionmentioning
confidence: 99%
“…The 3'-UTR of SNCA is highly conserved across species (Sotiriou et al, 2009) and few of the SNPs identified in this region exhibit sufficient heterozygosity for further study. However, alcohol-use phenotypes have been associated with SNCA 3'-UTR polymorphisms.…”
Section: Introductionmentioning
confidence: 99%